2009
DOI: 10.5194/acp-9-1899-2009
|View full text |Cite
|
Sign up to set email alerts
|

Automatic detection of ship tracks in ATSR-2 satellite imagery

Abstract: Abstract. Ships modify cloud microphysics by adding cloud condensation nuclei (CCN) to a developing or existing cloud. These create lines of larger reflectance in cloud fields that are observed in satellite imagery. An algorithm has been developed to automate the detection of ship tracks in Along Track Scanning Radiometer 2 (ATSR-2) imagery. The scheme has been integrated into the Global Retrieval of ATSR Cloud Parameters and Evaluation (GRAPE) processing chain. The algorithm firstly identifies intensity ridge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…Studies of ship track occurrence on a global scale with satellite observations was, to our knowledge, performed by two studies. Schreier et al [2007] used 1 year data to compile a global statistic of ship tracks identified by visual analysis, whereas Campmany et al [2009] utilized an automatic ship track detection algorithm. Both studies find accumulations of ship tracks over similar regions of the worlds' oceans with the exception that Campmany et al [2009] did not find any tracks off the coast of Africa (an updated version of the algorithm also finds some tracks off the coast of Africa (A. M. Sayer, personal communication, 2011)).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of ship track occurrence on a global scale with satellite observations was, to our knowledge, performed by two studies. Schreier et al [2007] used 1 year data to compile a global statistic of ship tracks identified by visual analysis, whereas Campmany et al [2009] utilized an automatic ship track detection algorithm. Both studies find accumulations of ship tracks over similar regions of the worlds' oceans with the exception that Campmany et al [2009] did not find any tracks off the coast of Africa (an updated version of the algorithm also finds some tracks off the coast of Africa (A. M. Sayer, personal communication, 2011)).…”
Section: Introductionmentioning
confidence: 99%
“…The retrievals have already been used to study ship tracks (Campmany et al, 2009;Sayer and Grainger, 2010) and study cloud-aerosol interactions (Bulgin et al, 2008). It is noted that, while the authors have applied the algorithm Table 1.…”
Section: A Poulsen Et Al: Cloud Retrieval Algorithmmentioning
confidence: 99%
“…Durkee et al, 2000;Ackerman et al, 2000;Campmany et al, 2009;Christensen and Stephens, 2011). Ship tracks provide an ideal experiment for isolating the impact of aerosols, as the polluted clouds are similar in origin and thickness to clean clouds in the surrounding cloud deck, although they may be elevated in height (Christensen and Stephens, 2011).…”
Section: Aerosol Indirect Effectsmentioning
confidence: 99%